2018
DOI: 10.3390/app8091664
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Protection Coordination Scheme for the Optimal Coordination of Overcurrent Relays Using a Nature-Inspired Root Tree Algorithm

Abstract: In electrical engineering problems, bio- and nature-inspired optimization techniques are valuable ways to minimize or maximize an objective function. We use the root tree algorithm (RTO), inspired by the random movement of roots, to search for the global optimum, in order to best solve the problem of overcurrent relays (OCRs). It is a complex and highly linear constrained optimization problem. In this problem, we have one type of design variable, time multiplier settings (TMSs), for each relay in the circuit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…The execution of WCA is implemented on three different network configurations and it was observed that the proposed WCA gives a better solution in all the contextual analysis. The detailed system descriptions of all three cases can be found in [2,26,29]. The purpose behind considering a single loop and multi-loop network is that depending upon different networks, the number of constraints, CTI and complexity varies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The execution of WCA is implemented on three different network configurations and it was observed that the proposed WCA gives a better solution in all the contextual analysis. The detailed system descriptions of all three cases can be found in [2,26,29]. The purpose behind considering a single loop and multi-loop network is that depending upon different networks, the number of constraints, CTI and complexity varies.…”
Section: Resultsmentioning
confidence: 99%
“…It reduces minimum operating time by 11.50 s and 0.97 s in comparison with the simplex method and root tree algorithm, respectively. It is found that WCA provides slightly improved net time gain relative to RTA, but as oppose to RTA, WCA takes fewer iterations [29]. The WCA gave less operating time and improved the performance of seven OC relay with optimized TDS.…”
Section: Comparison Of Wca With Simplex Methods and Root Tree Algorithmmentioning
confidence: 92%
See 1 more Smart Citation
“…Some studies have addressed the protection coordination in a loop distribution system. In [13], an optimal protection coordination method for the overcurrent relay in a loop power distribution system was proposed using the nature-inspired root tree algorithm. In [14], an optimization method for the time-dial setting of the directional overcurrent relay in the closed-loop power distribution system was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we address the protection issue considering the operation of the tie switch in the open-loop system. In [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], protection issues in a closed-loop system were addressed; however, the operation of the tie switch was not considered except in [1]. To solve the problem in [1], we propose a new protection scheme based on the coordination with a tie switch.…”
Section: Introductionmentioning
confidence: 99%